Implementation of C4.5 Algorithm for Disease Classification: Literature Review - Sari Siregar (SEAN Institute, 2024)
Several studies have shown that the C4.5 algorithm is capable of achieving a high level of accuracy in diagnosing various diseases. For example, a study by Konstas et al. (2010) showed that the C4.5 algorithm was capable of achieving an accuracy level of 89% in diagnosing coronary heart disease. This study aims to discuss the application of the C4.5 Algorithm in disease classification as has been done by previous studies. This study is a literature review, which includes references related to the cases or problems identified. The author uses data from a literature study, a method used to collect data or sources related to the topic discussed in a study. The results of this Algorithm literature review can help doctors diagnose diseases more quickly, accurately, and efficiently. However, it is important to remember that the C4.5 algorithm is only a tool, and cannot replace the diagnosis of a professional doctor.